2012
DOI: 10.1007/s00270-012-0388-y
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Embolization Versus Laparoscopic Uterine Artery Occlusion: The Outcomes of a Prospective, Nonrandomized Clinical Trial

Abstract: Both methods are effective in the treatment of women with future reproductive plans and fibroids not suitable for LM. UAE is more effective in causing complete ischemia of fibroids, but it is associated with greater risk of intrauterine necrosis. Both methods have low rate of serious complications (except for a high abortion rate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…Moreover, several observational studies comparing UAE to myomectomy concluded that both uterine‐sparing surgical treatment modalities are equally successful and with comparable clinical outcomes, while a prospective cohort study focusing on re‐intervention rates concluded that women undergoing UAE were more likely to need further invasive treatment. Furthermore, observational studies comparing UAE to LUAO concluded that both treatments have comparable effects on women's symptoms but UAE is more effective in causing complete ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several observational studies comparing UAE to myomectomy concluded that both uterine‐sparing surgical treatment modalities are equally successful and with comparable clinical outcomes, while a prospective cohort study focusing on re‐intervention rates concluded that women undergoing UAE were more likely to need further invasive treatment. Furthermore, observational studies comparing UAE to LUAO concluded that both treatments have comparable effects on women's symptoms but UAE is more effective in causing complete ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports from observational studies comparing UAE to myomectomy concluded that UAE is associated with increased risk of complications in pregnancy such as preterm delivery and malpresentation and with a trend towards higher rates of miscarriages and postpartum hemorrhage and hence the joint Standards of Practice Committee of the Cardiovascular and Interventional Radiological Society of Europe and the Society of Interventional Radiology suggested that future reproductive plans are a relative contraindication to UAE . Finally, observational studies were inconclusive in terms of reproductive outcomes following UAE or LUAO, with one reporting equal pregnancy outcomes between the two groups and another reporting higher risk of miscarriage following UAE .…”
Section: Discussionmentioning
confidence: 99%
“…As reduções médias dos volumes dos miomas dominantes após a EAU foram de 40,5% (SENA MARTINS et al, 2003), 31,1% (GHIARONI et al, 2013) e 22% (BERNARDO et al, 2011). Esses valores são comparáveis aos encontrados em estudos internacionais (MARA et al, 2012;CHOI et al, 2013). Bonduki et al (2009) observaram uma redução quantitativa e qualitativa significativa do colágeno nas lâminas histológicas dos miomas após EAU, comprovando redução da massa tumoral.…”
Section: Resultsunclassified
“…If the ovarian arteries are blocked besides uterus arteries during UAE, there is increased probability of FSH increase and menstrual disorders [35]. Mara compared UAE with laparoscopic uterine artery ligation to treat fibroma and concluded that there was no difference between two methods in terms of abortion rates and pregnancy rate and even birth weight was higher in embolization group [36]. Given that patients were young, increased FSH was not noticeable.…”
Section: Discussionmentioning
confidence: 99%